SAFETY STUDY ON STATE SHIPS AND COMMERCIAL SHIPS ACCORDING TO THE REQUIREMENTS OF SOLAS 1974 - Prasadja Ricardianto; Reza Fauzi Jaya Sakti; Honny Fiva Akira Sembiring; Zaenal Abidin (ABNUS Publisher, 2021)
The purpose of this study is to analyze the safety performance of state ships and commercial ships according to the requirements of Solas 1974. The requirements of Solas 1974 in the context of international shipping are mainly related to safety and security issues related to the tools and types of shipping safety. Application of the 1974 Solas Convention and the 2018 Solas Consolidation with the scope of discussion on international shipping is especially related to maritime protection. This study uses the Plan, Do, Check and Action (PDCA) evaluation model. The data was collected through the interview survey method and continued with statistical testing with the factor analysis technique. Respondents consisted of crews of commercial ships with a weight of over 500 GT and crews of pioneer ships as state ships anchored at the Port of Tanjung Priok. Research respondents totaled 57 crew members, consisting of 23 crew members of state ships and 34 crew members of commercial ships. The results of this research can be used as reference material in terms of safety and security as well as protection against environmental damage, in accordance with the transportation management system policy which includes; manuals, implementation policies, supporting implementation procedures, and work instructions for all stakeholders. The research output can be used as a basis for providing recommendations related to corrective actions to improve the marine transportation management system through the implementation of Solas 1974.